Teknologi Internet of Things (IoT) dalam Penyemprotan Insektisida Aglonema pada Greenhouse - Retno Devita; Ruri Hartika Zain; Ipriadi; Ondra Eka Putra; Sri Rahmawati (Universitas Putra Indonesia YPTK Padang, 2021)
Aglonema is a plant that is widely cultivated by ornamental plant lovers, because it has various species with varied and beautiful leaf patterns. Aglonema cultivation can be a business opportunity in agriculture because aglonema plants are in great demand but also because the prices offered vary from hundreds of thousands to millions of rupiah. Aglonema plant care is quite easy and simple. However, the wrong aglonema plant care such as irregular watering, excessive fertilizer application, and the wrong plant placement can make plants grow less optimally or even die. Greenhouse is a building that was formed to avoid and treat plants against various kinds of weather. Weather is the state of the atmosphere in a place at a certain time related to air temperature, sunlight, wind, rain and other air conditions. Thus, the types of plants that are not in accordance with the local climate, such as ornamental plants, vegetables and fruit, which have high economic value but are difficult to cultivate in outdoor areas, can be cultivated through climate control in the greenhouse. Various benefits such as controlling air temperature, adjusting humidity levels, to the interval between watering times can be adjusted easily. Internet of things (IoT) is a concept or program where an object has the ability to transmit or transmit data over a network without using the help of computer and human devices. With this IoT, spraying insecticides at the Greehouse for aglonema plants can be done automatically